Pengaruh Kualitas Bahan Baku dan Proses Produksi Terhadap Kualitas Produk di Elvan Fashion Production - Erik Nurjaman Sidik; Suci Putri Lestari; Depy Muhamad Pauzy (Journal of Management and Social Sciences, 2023)
This study aims to determine the effect of the quality of raw materials and production processes on product quality (Case Study on Elvan Fashion Production). The method used in this study is causality through a survey approach. With a research sample of 100 labor of Elvan Fashion Production. The data used is using primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that the quality of Elvan Fashion Production's raw materials had good criteria. The production process at Elvan Fashion Production has good assessment criteria, Elvan Fashion Production Product Quality has good criteria. Taken together the Quality of Raw Materials and Production Processes have a significant influence on Product Quality. Partially the Quality of Raw Materials has a significant influence on Product Quality. Partially, the production process has a positive and significant effect on product quality.